2016
DOI: 10.1016/j.celrep.2016.06.098
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-Dependent Dopaminergic Regulation of Calcium Channel Activity in the Axon Initial Segment

Abstract: G-protein coupled receptors (GPCRs) initiate a variety of signaling cascades depending on effector coupling. β-arrestins, which were initially characterized by their ability to “arrest” GPCR signaling by uncoupling receptor and G protein, have recently emerged as important signaling effectors for GPCRs. β-arrestins engage signaling pathways that are distinct from those mediated by G-protein. As such, arrestin-dependent signaling can play a unique role in regulating cell function, but whether neuromodulatory GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…7, but see Yu et al, 2010), channel modulation occurred only in D3R-expressing neurons, identified either through fluorescent tag (D3-Cre::Ai14) or electrophysiological identification (Type 3). Modulation was restricted to AIS-localized Ca V 3 channels, consistent with previous findings in D3R-expressing auditory brainstem neurons (Bender et al, 2010(Bender et al, , 2012Yang et al, 2016). Within these neurons, we observed a marked reduction of both evoked and spontaneous bursts (Bender and Trussell, 2009;Bender et al, 2012).…”
Section: Implications For Mpfc D3 Receptor Function In Health and Dissupporting
confidence: 79%
See 1 more Smart Citation
“…7, but see Yu et al, 2010), channel modulation occurred only in D3R-expressing neurons, identified either through fluorescent tag (D3-Cre::Ai14) or electrophysiological identification (Type 3). Modulation was restricted to AIS-localized Ca V 3 channels, consistent with previous findings in D3R-expressing auditory brainstem neurons (Bender et al, 2010(Bender et al, , 2012Yang et al, 2016). Within these neurons, we observed a marked reduction of both evoked and spontaneous bursts (Bender and Trussell, 2009;Bender et al, 2012).…”
Section: Implications For Mpfc D3 Receptor Function In Health and Dissupporting
confidence: 79%
“…In previous work in auditory brainstem, we found that D3Rs specifically modulate Ca V 3 calcium channels (Bender et al, 2010;Yang et al, 2016). Here, we found that AIS Ca was modulated only in D3ϩ/Type 3 cells.…”
Section: D3rs Are Expressed In a Distinct Subset Of Mpfc Pyramidal Cellsmentioning
confidence: 42%
“…S9). Longer activation of the receptor evokes stable binding of β-arrestin and augments ERK signaling, a molecular mechanism that could be involved in modulation of ion channels (46,47) and formation of long-term memories (30,39,48). Evidently, by itself β-arrestin 1, but not β-arrestin 2, can act directly on plasma membrane ion channels (49).…”
Section: Discussionmentioning
confidence: 99%
“…Converging lines of evidence suggest that the AIS is a highly dynamic structure, exhibiting structural plasticity over different timescales ranging from a few hours to several days (7)(8)(9)(10)(11)(12)(13)(29)(30)(31). Various elegant studies used typical triggers of plasticity such as sensory deprivation, optogenetic stimulation, or high-K + -induced depolarization (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Long considered to be the trigger zone for AP initiation (28), the AIS was regarded as a static and rigid structure encompassing ion channels anchored to a scaffolding and cytoskeletal protein network. Now, it is recognized that the AIS is a highly dynamic structure, capable of structural and functional plasticity and continuously adapting to changes in neuronal activity (8,12,(29)(30)(31). In 2010, two seminal studies found that changes in neuronal activity could lead to AIS relocation or resizing as a new mechanism of slow homeostatic adaptation (32,33).…”
mentioning
confidence: 99%